2017
DOI: 10.1111/1365-2664.12905
|View full text |Cite
|
Sign up to set email alerts
|

Forest restoration as a double‐edged sword: the conflict between biodiversity conservation and pest control

Abstract: 1. Forestry has markedly changed a large proportion of the world's boreal forests, often with negative effects on biodiversity. As a result, forest restoration is increasingly implemented to counteract the negative effects. However, restoration measures aimed at mimicking natural disturbance regimes could simultaneously increase the risk of unwanted negative effects, such as damage by forest pest species. This study compares the effect of two restoration methods (prescribed burning and gap-cutting), on both bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…Fire induces profound changes in stand characteristics, which influence tree substrate availability and quality (Stokland et al 2012, 2018. This may result in changes in both the abundance and assemblage composition of saproxylic insects, the main food source of Threetoed Woodpeckers (Saint-Germain et al 2004a, b, 2008, Hyvärinen et al 2009, Boucher et al 2012, Hekkala et al 2014, Kärvemo et al 2017. It has been suggested that burning homogenizes the quality of tree species in terms of nutrients and structure, making them more equal for saproxylic insects and reduces differences in insect diversity among tree species (Wikars 2002, Toivanen andKotiaho 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fire induces profound changes in stand characteristics, which influence tree substrate availability and quality (Stokland et al 2012, 2018. This may result in changes in both the abundance and assemblage composition of saproxylic insects, the main food source of Threetoed Woodpeckers (Saint-Germain et al 2004a, b, 2008, Hyvärinen et al 2009, Boucher et al 2012, Hekkala et al 2014, Kärvemo et al 2017. It has been suggested that burning homogenizes the quality of tree species in terms of nutrients and structure, making them more equal for saproxylic insects and reduces differences in insect diversity among tree species (Wikars 2002, Toivanen andKotiaho 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In these operations, the amount of post-harvest CWD is important (Joelsson 2017). Gap felling, with gaps 20 m in diameter, benefits cambium consumers, particularly bark beetles (Scolytidae: Scolytinae), but has minor effects on the overall composition of the beetle assemblage (Hjältén et al 2017b;Kärvemo et al 2017). Specifically, xylophages of fresh CWD benefit from felling, apparently due to the rich pulse of slash and stumps, whereas some other species groups may decline, such as mycetophages (Heikkala et al 2016b;Jokela et al 2019; Table 2).…”
Section: Saproxylic and Other Actively Flying Beetles Short-term Effementioning
confidence: 99%
“…On the other hand, burning affects some bark beetles negatively (Toivanen and Kotiaho 2010), so prescribed burning may also decrease risks for economic damage (though see, e.g., Kärvemo et al 2017).…”
Section: Prescribed Burningmentioning
confidence: 99%
“…1) (DeFries et al 2004). In addition, logging is a common strategy in forest management to guard against the spread of species targeting decomposing wood (Karvemo et al 2017). For example, bark beetles are natural inhabitants of old-growth trees and their control has started a debate between loggers and environmentalists who disagree on the best way to combat them (Grotta 2013;Stokstad 2017).…”
Section: Introductionmentioning
confidence: 99%